An SI-traceable multilateration coordinate measurement system with half the uncertainty of a laser tracker. (1st June 2023) - Guillory, Joffray; Truong, Daniel; Wallerand, Jean-Pierre; Svantesson, Claes-Göran; Herbertsson, Magnus; Bergstrand, Sten
Abstract: We have validated the performance of a prototype coordinate measurement system based on multilateration by comparing it to a laser tracker, i.e. a well-proven instrument widely used in the industry. After establishing the uncertainty budget of the different systems, we performed position measurements with both instruments on common targets. Using the estimated uncertainties associated with the measurements, we found that the multilateration system provided lower position uncertainties than the laser tracker: on average 18 µm versus 33 µm for distances up to 12 m. The uncertainties represented by confidence ellipsoids are compatible between the two systems: for confidence regions of 95% probability, they overlap as expected, i.e. in 94% of the cases. We also measured the length of a 0.8 m long reference scale bar with the multilateration system at an error of only 2 µm. This cross-comparison is a new and key step in the characterization of this SI-traceable multilateration system.